Self-Reported sleep duration and its correlates with sociodemographics, health behavioural, poor mental health, and chronic conditions in rural persons 40 years and older in South Africa - Peltzer, Karl; Pengpid, S. (International Journal of Environmental Research and Public Health, 2018)
This study aims to investigate sleep duration and its association with sociodemographic, health behaviour, mental health, and chronic disease factors among rural individuals 40 years and older in South Africa. Cross-sectional data from the “Health and Aging in Africa: A Longitudinal Study of an INDEPTH community in South Africa” (HAALSI) baseline survey were analysed. Socio-demographic, clinical, health, and sleep duration data were collected. The total sample included 4725 persons 40 years and older (mean age 61.5 years, SD = 13.0, age range of 40–111 years) in one sub-district in rural South Africa. The mean sleep duration was 8.28 ± 1.93 h. Short (<7 h) and long (≥9 h) sleepers accounted for 13.1% and 40.0% of the sample, respectively. In adjusted multinomial logistic regression, greater wealth status (p < 0.05), inadequate fruit and vegetable consumption (p < 0.001), and depressive symptoms (p < 0.05) were associated with a higher odds and physical inactivity (p < 0.05) with a lower odds of short sleep duration. Being male (p < 0.001) and depressive symptoms (p < 0.001) were associated with a higher odds and being 50 to 69 years old (p < 0.01), having Grade 1 to 11 education (p < 0.05), and greater wealth status (p < 0.001) were associated with a lower odds of long sleep duration. In adjusted multinomial logistic regression, compared to normal sleepers, long sleepers were more likely to have myocardial infarction (p < 0.05). In unadjusted analysis, compared to normal sleepers, short sleepers were more likely to have cataracts (p < 0.05). This study found that a significant proportion of rural dwellers 40 years and older in South Africa had a short sleep duration and a high proportion had a long sleep duration. Some associations, such as depression and myocardial infarction, with short and/or long sleep duration were confirmed, while no associations were found for many chronic conditions. Keywords: sleep duration; health behaviour; mental health; chronic conditions; persons 40 years and older; rural South Africa; HAALSI
International Journal Environmental. Research and Public Health 2018, 15, 1357
Keywords: Sleep duration; Health behaviour; Mental health; Chronic conditions; Persons 40 years and older; Pural South Africa; HAALSI; Hypnotics